Polish pregnant women’s knowledge on early childhood caries prevention and oral hygiene in children - Katarzyna Domosławska-Żylińska; Magdalena Łopatek; Magdalena Krysińska-Pisarek; Paulina Wiśniewska (BMC Public Health, 2024)
Abstract Background Early childhood caries (ECC) is one of the most common chronic diseases among children. In Poland 86.9% of six-year-olds have ECC. One of the factors determining adherence to ECC prophylaxis and oral hygiene is mothers’ knowledge. The aim of this study was to assess the level of knowledge demonstrated by pregnant women about ECC prevention and oral hygiene, and to analyse the determinants of this knowledge. Methods A quantitative survey was conducted using Computer Assisted Telephone Interview technique on a randomly selected representative sample of 1,000 women over the age of 18 in their second and third trimesters of pregnancy. The significance level was established at 0.05 and p-values were presented as: p < 0.05, p < 0.01 and p < 0.001. Results The highest percentage of wrong or “I don’t know” answers were related to questions about: the number of free dental check-ups for children (76.8%), the date of the child’s first visit to the dentist (66.5%), the age when the child has mixed dentition (72.2%). Women with higher education had better knowledge than women with lower or secondary education. Women with good and very good financial situation showed a higher level of knowledge compared to women with average, bad and very bad financial situation. Conclusions When developing prevention strategies and educational programs as part of prenatal care for women to reduce the incidence of ECC, it is important to take into account the identified areas that need support and specific target groups (mothers with lower socioeconomic status).